Representation Of Moral Messages In The Short Film 'Self' (2024) By Raihan Ananda Pratama: A Peircean Semiotics Analysis - Eko Hadi Prayitno; Juju Masunah; Zakarias S. Soeteja; Hery Supiarza (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This article is a description of the results of a semiotic study of a short film entitled